IMPLEMENTASI PEMBAGIAN HARTA WARISAN PADA MASYARAKAT ISLAM - Teguh Dermawan; Supardin; Istiqamah (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
This study discusses the Implementation of the Division of Heritage Assets in the Islamic Community of Papalang District, Mamuju Regency (Case study 2020-2022). From the subject matter, the author formulates several sub-problems. First, the understanding of the Islamic community of Papalang district about inheritance and the second, the problem of the division of inheritance in Papalang District, Mamuju Regency. The type of research that the author uses is field research or can also be called qualitative research, field research carried out by observation methods, interviews, and describing the facts that occur in the field with the legal research approach used, namely the juridical normative approach and the empirical approach, which is an approach related to the Islamic legal view of how the process of inheritance division is. The second approach is an approach related to direct observation made by researchers to see and observe habits in the community about the process of distributing inheritance assets. The results of this study show that in fact, people tend to prefer to divide inheritance with customary and customary laws. This is done by the community for generations because the method used will further minimize disputes between heirs. The custom of the Islamic community in Papalang District was formed due to the lack of understanding of Islamic law which gave birth to the paradigm that the division of inheritance property does not have to be with Islamic law because the obligation is not like other worship services such as prayer, fasting, zakat etc. The implication of this study is that it is expected that all elements can abandon all forms of customs outside of Islamic law. In addition, the government must also take part and play an active role in providing a forum in the form of socialization so that people who do not understand can be enlightened and return to Islamic law. And it is also hoped that this research can provide legal references in the process of dividing inheritance assets